Spirituality, forgiveness and self-esteem throughout adulthood in France - Agli Océane; Bailly Nathalie; Cuervo-Lombard Christine-Vanessa (Archives of Gerontology and Geriatrics Plus)
Purpose: It appears that spirituality, forgiveness, and self-esteem are important values which transcend human actions. This transversal study aims to observe spirituality, forgiveness, and self-esteem during aging. Methods: A quantitative protocol was conducted with 206 participants divided into two groups: younger adults (M = 23.05 years old) and older people (M = 73.09 years old). Three tests measured spirituality, forgiveness and self-esteem. Principal results: Results showed that older people have higher scores than younger adults in spirituality (peace dimension), forgiveness (transcendence and emotional factors) and self-esteem. Moreover, all dimensions of spirituality (peace, mean, faith) were correlated with the transcendence and emotional factors of forgiveness and with self-esteem during aging. Major conclusion: It seems that with age, individuals have a better self-esteem linked to more pronounced spiritual needs (sense of peace, meaning of life, faith) and manage to forgive more unconditionally with less resentment than younger people.